Analisis progeny test untuk menghitungnilai pemuliaan pejantan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
A Progeny Test Program was started in 1987 by BIB Singosari, using three imported bulls. The purpose of this study is to analyses the Breeding Value of those 3 bulls. The production records of the daughters born in 1988 located at East Java (Pasuruan, Jombang and Malang) and West Java (Lembang, Cisarua and Pengalengan) were used in this study. A total of 136 production data up to 1992 were used in this analysis. The heritability of milk production was found to be 0,32. By using this value, it was found that the Breeding Value of the 1st, 2nd and 3rd bulls were 3.923,98, 5.009,36 and 4.286,14 kg/lactation, respectively. The relative accuracy of the 1st bull was less than one, due to the tact of data. The average of milk production found in this study were 3.997,41 and 5.269,46 kg/lactation for East and West Java, respectively. There was a significant difference (P < 0,05) between locations and a highly significant difference (P < 0,01) between bulls. The reproductive efficiency were 92,29% and 90,60% for East and West Java, respectively, which means a very good reproductivity. The age of first calving found in this study were 28,69 and 28,93 months of age for East and West Java, respectively. A conclusion can be made from this study that there will be no danger on the first age of calving by crossing the local cows to imported bulls.